Modeling of Linearized Generator Inertia Constraints for Unit Commitment - Sung-Eun Kim; Yeong-Han Chun (Energies, 2024)
This study presents a novel approach to modeling linearized inertia constraints of generators, considering frequency stability, and applies it to the unit commitment (UC). Specifically, we modeled the average rate of change of frequency (RoCoF) constraint and the minimum frequency constraint using the analytical expression derived from the reduced frequency response (RFR) model. We also considered the load-damping constant as a variable. As the power system has different nonlinear characteristics according to its operating status, the system can be expressed as several different systems. Each subsystem, with its own properties at a given operating point, is modeled as a single-machine system, categorized by pumped storage hydropower (PSH) status. The minimum frequency of each subsystem is determined by its individual machine time constant. We incorporated an additional constraint to ensure the quasi steady-state performance of frequency. This constraint can be omitted when it is not necessary. The proposed concepts have been validated on the Korean Power System. The UC, with the proposed inertia constraints, can secure system inertia and primary frequency response (PFR) that satisfies frequency stability. Our proposed method is more efficient in securing inertia and PFRs and more economical in terms of generation cost compared to existing methods.